Journal of Neurophysiology and Neurological Disorders 2019
DOI: 10.17303/jnnd.2019.5.204
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Rich Plasma Membrane Submicrodomains Can Be a Major Extram- itochondrial Source of Reactive Oxygen Species in Partially Depolarized Mature Cerebellar Granule Neurons in Culture

Abstract: Excessive production of reactive oxygen and nitrogen species can elicit neuronal cell death and brain neurodegeneration. In previous studies, we have shown that lipid rafts nanodomains of mature cerebellar granule neurons (CGN) contain most of the neuronal nitric oxide synthase and also of cytochrome b 5 reductase isoform 3 (Cb5R3), which is the component of neuronal synaptic plasma membrane vesicles that generates superoxide anion upon stimulation by cytochrome c. In this work, we show that CGN maturation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Increasing evidence suggests that Aβ peptides are internalized in neuronal cells through different pathways, which also depend on the cell type [ 22 , 58 , 59 ]. It has been reported that neuronal lipid rafts microdomains play a major role in Aβ formation/oligomerization and Aβ uptake by neurons, reviewed in [ 60 ], and we showed in a previous study that mature cerebellar granule neurons express high levels of lipid rafts markers like cholera toxin B binding sites, caveolin-1, flotillin, and HRas [ 61 , 62 ]. In contrast, we found in this work that HT-22 cells were not stained with cholera toxin B-Alexa488, demonstrating the lack of lipid rafts in this mouse hippocampal cell line HT-22 [ 63 ].…”
Section: Discussionmentioning
confidence: 85%
“…Increasing evidence suggests that Aβ peptides are internalized in neuronal cells through different pathways, which also depend on the cell type [ 22 , 58 , 59 ]. It has been reported that neuronal lipid rafts microdomains play a major role in Aβ formation/oligomerization and Aβ uptake by neurons, reviewed in [ 60 ], and we showed in a previous study that mature cerebellar granule neurons express high levels of lipid rafts markers like cholera toxin B binding sites, caveolin-1, flotillin, and HRas [ 61 , 62 ]. In contrast, we found in this work that HT-22 cells were not stained with cholera toxin B-Alexa488, demonstrating the lack of lipid rafts in this mouse hippocampal cell line HT-22 [ 63 ].…”
Section: Discussionmentioning
confidence: 85%
“…Green fluorescence (GF) images of Control and A1 cells were acquired with an excitation filter of 470 nm and a 510 nm dichroic mirror/520 nm emission filter, using the exposure times indicated for each case in the legends of the figures. Quantitative analysis of the average fluorescence intensity per pixel of selected neuronal soma was performed via HCImage software using the ROI tool, as in previous works [ 30 , 60 , 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%